Effect of Pibaijin herbal cream external application combined with modified transparent dressing in the treatment of contact dermatitis after PICC catheterization (皮白金草本乳膏外涂联合改良透明贴膜换药治疗PICC置管并发接触性皮炎的效果观察) - XU Xingna (徐兴娜) (Journal of International Translational Medicine Limited, 2022)
Objective To explore the effect of Pibaijin herbal cream external application combined with modified transparent dressing in the treatment of contact dermatitis after peripherally inserted central catheter (PICC)catheterization. Methods From October 2019 to October 2021, 73 patients with contact dermatitis after PICC catheterization were selected, and divided into experimental group (n=42) and control group (n=31). The experimental group was treated with Pibaijin herbal cream external application combined with modified transparent dressing. The control group was treated with dexamethasone plus gentamicin combined with modified transparent dressing. The itching disappearance time, dermatitis subsidence time, unplanned withdrawals of catheters, skin pigmentation, comfort of patients and retention of the catheter were observed and compared between two groups. Results The itching disappearance time, dermatitis resolution time, and skin pigmentation rate were significantly lower in experimental group than those in the control group (P＜0. 01). Patients in the experimental group had a higher level of satisfaction and lower rate of unplanned withdrawals of catheter compared with those in the control group (P＜0. 01). Conclusion Pibaijin herbal cream external application combined with modified transparent dressing has better effect on treating contact dermatitis after PICC catheterization. It could reduce the rates of unplanned catheter withdrawal and skin pigmentation, and improve the comfort degree of patients. (目的 探讨皮白金草本乳膏外涂联合改良透明贴膜换药治疗经外周静脉穿刺中心静脉置管(PICC)并发接触性皮炎的效果。方法 选取2019年10月～2021年10月科室收治的PICC置管后并发接触性皮炎的患者73例, 分为研究组42例和对照组31例。对照组采用地塞米松加庆大霉素外涂联合改良透明贴膜换药, 研究组采用皮白金草本乳膏外涂联合改良透明贴膜换药。观察两组患者痒感消失时间、皮炎消退时间、是否脱管、有无皮肤色素沉着、患者带管舒适度以及导管保留情况。结果 与对照组相比, 研究组痒感消失时间、皮炎消退时间较短, 皮肤色素沉着发生率较低, 差异有统计学意义(P＜0. 01); 研究组患者带管舒适度高, 非计划拔管发生率低, 与对照组相比, 差异有统计学意义(P＜0. 01)。结论 应用皮白金乳膏外涂联合改良透明贴膜换药, 可以有效治疗PICC置管并发接触性皮炎, 降低患者脱管率和皮肤色素沉着率, 提高带管舒适度。)